PENGARUH PROFITABILITAS, STRUKTUR ASET,KEPUTUSAN INVESTASI, DAN RISIKO BISNISTERHADAP STRUKTUR MODAL - Zahroh, Fatimatus; Fitria, Astri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Capital structure is one of the standards of trust level of the investors since the good and bad of the capital structure will have a direct effect to the financial position of the company. The purpose of this research is to test the influence of profitability, asset structure, invesment decision and bussiness risk to the capital structure.The samples are food and beverages companies which are listed in Indonesia Stock Exchange (IDX) in 2011-2014 periods. The sample collection techique has been done by using non probability sampling and purposive sampling method, and based on the determined criteria, 11 companies have been selected as samples. This researh has been done by using classic assumption and multiple linear reggressions analysis.The result of the research shows: (1) the profitability has no influence to the capital structure, (2) that structure of assets has influence to the capital structure (3) investment decisions has no influence to the capital structure, and (4) the business risk has no influence to the capital structure.Keywords: Profitability, Asset Structure, Invesment Decision, Business Risk, Capital Structure.